The Effect of Giving Positive Affirmations on Stress Levels in Adolescents - Sofia Mawaddah; Nova Indriani (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Mental health is still one of the significant problems in the world, including in Indonesia (Ministry of Health of the Republic of Indonesia, 2016). According to WHO (2016), there are 35 million people who experience depression and stress. The purpose of this study to find out if there is an influence on the positive affirmation of stress levels in adolescents. This study used a pre-experimental design on 55 adolescent respondents as a research sample, which was taken using one-group pretest-posttest technique. Data collection using a questionnaire using the T-test test. Based on the results of the t-test, it was obtained that p value = 0.000 (p < 0.05) which the average stress level before positive affirmation was 18.22 (SD = 0.904). The average stress level after positive affirmation was 14.42 (SD = 0.711), which means that there is an effect of giving positive affirmation interventions on stress levels in adolescents.